1994
DOI: 10.1093/jnci/86.21.1600
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Population-Based Assessment of Cancer Risk in First-Degree Relatives of Cancer Probands

Abstract: This study represents a unique comprehensive population-based study of familial cancer. The familial associations reported here will be useful in generating hypotheses about specific genetic and environmental factors that can be tested in genetic linkage and case-control studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
643
7
16

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 927 publications
(717 citation statements)
references
References 0 publications
51
643
7
16
Order By: Relevance
“…In contrast, in the present study, the risk remained above 2 even over age 65 years, although it was over 5 below age 45 years. A risk above 2 over age 60 years was also observed in a comprehensive population-based study of familial cancer based on the Utah population database (Goldgar et al, 1994). In that study, as in the present one, the risk was also elevated for rectal cancer.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, in the present study, the risk remained above 2 even over age 65 years, although it was over 5 below age 45 years. A risk above 2 over age 60 years was also observed in a comprehensive population-based study of familial cancer based on the Utah population database (Goldgar et al, 1994). In that study, as in the present one, the risk was also elevated for rectal cancer.…”
Section: Resultssupporting
confidence: 81%
“…A previous study in northern Italy (La Vecchia et al, 1992) also found an association with gastric cancer, and the Utah Population Database (Goldgar et al, 1994) with leukaemias. The associations with bone and kidney cancer for colon in this study are probably because of misclassification of metastases and/or chance.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This is likely due to shared environmental and genetic factors. The overall frequency of cancers among first-degree relatives of cancer patients has been shown to exceed that of the general population [8]. Synchronous and metachronous malignancies (double primaries) are a hallmark of inherited cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The American Cancer Society estimated that in 1995 more than 130 000 new cases of CRC would be diagnosed in the USA and that there would be 54 900 deaths from the disease (American Cancer Society, 1995). CRC onset and its progression has been studied extensively at the molecular (Bos et al, 1987;Forrester et al, 1987;Vogelstein et al, 1988;Burmer and Loeb, 1989;Delattre et al, 1989;Kern et al, 1989;Vogelstein et al, 1989;Fearon and Vogelstein, 1990;El-Deiry et al, 1991;Oudejans et al, 1991;Houlston et al, 1992;Laurent-Puig et al, 1992;Offerhaus et al, 1992;Sharrard et al, 1992;Bell et al, 1993;Finkelstein et al, 1993a and b;McLellan et al, 1993;Peltomaki et al, 1993;Urosevic et al, 1993;Breivik et al, 1994;Dix et al, 1994;Moerkerk et al, 1994;Morrin et al, 1994;Tanaka et al, 1994;Giaretti et al, 1995;Laird et al, 1995;Lewis et al, 1996;Span et al, 1996) and genetic (Woolf et al, 1958;Macklin et al, 1960;Houlston et al, 1992;Zhao and Le Marchand, 1992;Peltomaki et al, 1993;Goldgar et al, 1994;Lewis et al, 1996) levels and there is a commonly accepted model relating tumour grade according to Dukes' stage (Dukes, 1932) to specific DNA changes …”
mentioning
confidence: 99%